Labor, Leisure, and the Yeoman in Coleridge's and Wordsworth's 1790s Writings - Malachuk, Daniel (Romanticism on the Net, 2002)
AbstractIn the republican tradition, from Aristotle through James Harrington, leisure was essential to the cultivation of civic virtue; labor—associated with the oikos rather than the polis—was not. In the late eighteenth-century, however, some democratic republicans celebrated the yeoman, who cultivated civic virtue through both his leisure and his labor. As a union of ancient opposites, the yeoman was a compelling but politically unstable character in republican theory, as suggested in the work of Jefferson and Rousseau. The same is true of the yeoman in Coleridge's and Wordsworth's early writings. Both writers began the 1790s convinced that in the yeoman one found the political realization of both labor and leisure. By mid-decade, Wordsworth no longer believed this, emphasizing instead the moral—rather than civic—value of landed property (the site of labor and leisure). Coleridge, too, came to question the significance of landed property, but not the significance of civic virtue; instead, he investigated new means to realizing that political condition, including a free press and a clerisy.